Oral Computer-Mediated Interaction Between L2 Learners: It’s About Time! - Yanguas, Íñigo (Language Learning and Technology, 2010)
This study explores task-based, synchronous oral computer-mediated communication (CMC) among intermediate-level learners of Spanish. In particular, this paper examines (a) how learners in video and audio CMC groups negotiate for meaning during task-based interaction, (b) possible differences between both oral CMC modes and traditional face-to-face (FTF) communication, and (c) how this oral computer mediated negotiation compares to that found in the text-based CMC literature. Fifteen learner-to-learner dyads were randomly assigned to an audio group, a video group, and a FTF control group to complete a jigsaw task that was seeded with 16 unknown lexical items. Experimental groups used Skype, free online communication software, to carry out the task. The transcripts of the conversations reveal that oral CMC groups do indeed negotiate for meaning in this multimedia context when non-understanding occurs between speakers. In addition, results showed differences in the way audio and video groups carry out these negotiations, which were mainly due to the lack of visual contact in the audio group. No differences were found between video and FTF groups. Furthermore, oral CMC turn-taking patterns were shown to be very similar to FTF patterns but opposite to those found in written synchronous CMC. Oral CMC interaction patterns are shown to be more versatile.